OP0216 Safety of Tocilizumab, Interleukin-1 Inhibitors and Etanercept in 262 Systemic Juvenile Idiopathic Arthritis Patients. (15th July 2016) - Horneff, G.; Schultz, A.C.; Hospach, A.; Ganser, G.; Foeldvari, I.; Thon, A.; Trauzeddel, R.; Weller, F.; Minden, K.; Haas, J.P.
Abstract : Background: Since the approval of first biologics for treatment of JIA, surveillance in Germany is monitored prospectively by the BIKER registry. Objectives: To evaluate the safety of Tocilizumab (TOC), IL-1 inhibitors (Anakinra & Canakinumab) and Etanercept (ETA). Methods: Safety assessments were based on adverse events reports. Results: 205 sJIA pts received 269 treatment courses with biologics (TOC 71, Anakina 36, Canakinumab 19, ETA 143 and 57 pts. received MTX only. Median age was lower In the MTX cohort (4.8y) than with ETA (8.2); TOC (9.6); IL-1i (8.2) as was the disease duration. ETA was started in 80% of pts before 2008 while in the TOC cohort all pts and in the IL-1i cohort 74% started therapy after 2008. Pre-treatment consisted of systemic steroids in 75% starting MTX and in all patients starting biologics. Initial concomitant treatment with systemic steroids was significantly less frequent with TOC (44%, p<0, 001) and IL-1i (44%, p<0.001) compared to 83% with ETA and 82 in MTX cohort. There were 30 adverse events (AE) in the MTX cohort, 71 in the ETA, 118 in the TOC and 81 in the IL-1i cohort. Rate of AE (per patient-year) was significantly higher in the TOC (RR 4.64; p<0.0001) and IL-1i-group (RR 3.04; p<0.01) (Table) and serious AE were also more frequent upon TOC (RR 5.5; p<0.01) and IL1i (6.39; p<0.01) but not upon ETA compared to the MTX cohort. There were 13 reports about Macrophage activation syndrome. Rates were not different. Of 125 infections, 13 were reported as serious. The infection rate was significantly higher in the TOC cohort (RR 4.3; p<0.001)and IL-1i cohort (RR 2.93; p<0.001) and significantly lower with ETA (RR 0.39; p<0.01) than in the MTX cohort. Hodgkin's lymphoma, Crohn's disease and demyelination occurred once in the ETA cohort, one case with a depression with suicidal thoughts occurred with IL-1i. Intolerance led to discontinuation of ETA in 3.5%, TOC in 8.3% and IL-1i in 2%. 2 pts died (septic shock & MAS) not related to biologics. Conclusions: Higher rates of safety signals, especially infections were noted upon treatment with TOC and IL-1i. Beside infections, disease reactivation and MAS, further adverse events were rare and overall tolerability was acceptable. However, steroids were markedly spared upon IL6- and Il-1 inhibitors. Disclosure of Interest: G. Horneff Grant/research support from: Abbvie, Roche, Chugai, Pfizer, A. Schultz: None declared, A. Hospach: None declared, G. Ganser: None declared, I. Foeldvari: None declared, A. Thon: None declared, R. Trauzeddel: None declared, F. Weller: None declared, K. Minden: None declared, J. Haas: None declared